Rights of personality in Scots Law a comparative perspective - Whitty, Niall R.; Zimmermann, Reinhard, 1952 October 10- (Dundee : Dundee University Press, 2009)
This title considers topical issues relating to rights of privacy and other rights of personality in Scots private law in its unique historical and comparative context as Europe's only 'mixed' (Roman/English) system of private law. Themes include the creation of a system of private law rights of personality; the introduction of rights of privacy; the impact of the European Convention on Human Rights; the debate on rights of publicity; and the operation of personality rights in important specific areas of law such as intellectual property and medical law.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Personality (Law) -- Scotland; Privacy, Right of -- Scotland; Law; Laws of specific jurisdictions & specific areas of law